SHIPYARD WELDING EMISSION ESTIMATION FOR DIFFERENT ELECTRODE AND SHIP TYPES - Mert, Tolga; Celebi, Ugur Bugra; Bilgili, Levent; Ekinci, Serkan (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2019)
Although welding is an essential process in shipbuilding, welding related air emissions cause remarkable problems for worker health and environment. A great number of different electrodes are used during an ordinary ship building or repairing process. Shielded Metal Arc Welding (SMAW) and Gas Metal Arc Welding (GMAW) are most frequently used welding methods in shipyards and it is well known that gaseous emissions and fumes formed during welding processes may have effect on global climate change and may cause various diseases on workers. In this study, the total amount of covered electrodes used during chemical tanker's and container ship's manufacturing process is obtained and the amount of the emissions to air is estimated with the help of fume formation rate experiments. Emission amount/deadweight ton ratios are also calculated in order to investigate the efficiency of manufacturing per load.
Keywords: Shipbuilding; welding; emission estimation; PULMONARY EXPOSURE; FUME; MANGANESE; STEEL; Environmental Sciences & Ecology